Dimensionamento estrutural de galpão metálico treliçado considerando treliças Howe e Pratt - Costa, Matheus Silva (2023)
In the design of trussed steel shed structures, there are several alternatives for structural design. The adoption of concepts for project rationalization are important to achieve results that meet safety and economy criteria. Thus, the aim of this work is to compare the structural performance of Howe and Pratt trusses. For this, a shed was designed with Howe and Pratt truss solutions. For both types of truss, the modeling of the structure's geometry, the load report, the structural dimensioning and the verification of the efforts obtained in the mCalc3D and Ftool software were carried out. The costs of the profiles used in the dimensioned elements were also considered. The results admired that the Howe truss model showed greater steel savings when compared to the Pratt truss model, since its geometry contributes to the greater effects of shocks being concentrated in bars that have a shorter buckling length, to the criticism of the design that has the suction wind as the predominant action. In this way, the present work generates tributes that can guide engineers and architects in the definition of systems developed for trussed steel sheds.